Outcomes of Emergent Inguinal Hernia Repair in Veteran Octogenarians. Issue 5 (May 2014) - Huerta, Sergio; Pham, Thai; Foster, Scott; Livingston, Edward H.; Dineen, Sean
Outcomes from emergent inguinal hernia (IH) repair in veteran octogenarians are not well described. We reviewed outcomes for this cohort from 2005 to 2012 at the VA North Texas Health Care System. There were 15 emergent (Group I) and 86 elective (Group II) operations performed in octogenarians. Age and American Society of Anesthesiologists status were similar in both groups. The rate of minor and major complications was higher in Group I compared with Group II (33 and 19% vs 22 and 2%, respectively; both P s < 0.001). Hospital length of stay (LOS) and intensive care unit LOS were also longer in Group I compared with Group II (6.7 ± 7.0 and 2.5 ± 4.4 vs 0.8 ± 1.9 and 0.12 ± 0.6 days, respectively; both P s < 0.001). Thirty-day mortality was 13 per cent for Group I and 0 per cent for Group II. Despite the high rate of comorbid conditions in our group, the risk associated with elective repair of IH was not prohibitive. In contrast, we observed that 15 per cent of patients presented with an incarcerated hernia during the study period and the mortality rate was 13 per cent in this cohort. Factors that might predict incarceration in veteran octogenarians need to be further investigated.